Neuroergonomic Assessment of Hot Beverage Preparation and Consumption: An EEG and EDA Study - Sargent, Amanda; Watson, Jan; Ye, Hongjun; Suri, Rajneesh; Ayaz, Hasan (Frontiers in Human Neuroscience, 2020)
Neuroergonomics is an emerging field that investigates the human brain in relation to behavioral performance in natural environments and everyday settings. This study investigated the body and brain activity correlates of a typical daily activity, hot beverage preparation, and consumption in a realistic office environment where participants performed natural daily tasks. Using wearable, battery operated and wireless Electroencephalogram (EEG) and Electrodermal activity (EDA) sensors, neural and physiological responses were measured in untethered, freely moving participants who prepared hot beverages using two different machines (a market leader and follower as determined by annual US sales). They later consumed the drinks they had prepared in three blocks. Emotional valence was estimated using frontal asymmetry in EEG alpha band power and emotional arousal was estimated from EDA tonic and phasic activity. Results from 26 participants showed that the market-leading coffee machine was more efficient to use based on self-reports, behavioral performance measures, and there were significant within-subject differences in valence between the two machine use. Moreover, market leader user interface led to greater self-reported product preference, that was further supported by significant differences in measured arousal and valence (EDA and EEG respectively) during coffee production and consumption. This is the first study that uses a multimodal and comprehensive assessment of coffee machine use and beverage consumption in a naturalistic work environment. Approaches described in this study can be adapted in the future to other task-specific machine usability and consumer neuroscience studies.